Android Application of English Learning as Learning Media for Junior High School Students - Lahmudin Sipahutar; Nursyah Handayani (International Journal of Computer and Information System (IJCIS), 2022)
One form of technological advances in computers is a mobile device. At this time English is a very important requirement in all fields of education and work even in daily life, because English itself has become an international language where most countries use this language. However, most junior high school students often have difficulty in learning English. This research aims to create an English learning application based on the existing curriculum using Adobe Animate CC 2017 which is offline. The stages used to make the application in this study are problem analysis, problem, problem solving strategies and system design. The global system design uses UML modeling which consists of Use case Diagrams, Story Boards, Activity Diagrams, Sequence Diagrams and Flow Charts. This application makes it easier for junior high school students to learn English so that it helps make it easier for teachers to convey material and also this application considers all aspects of development, is meaningful, interesting, and functional. features after testing on several smartphone devices.